2005
DOI: 10.1021/jf048174d
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin I Converting Enzyme Inhibitory Peptides from In Vitro Pepsin−Pancreatin Digestion of Soy Protein

Abstract: Angiotensin I converting enzyme (ACE) inhibitory activity was determined in the soy protein isolate (SPI) digest produced by in vitro pepsin-pancreatin sequential digestion. The inhibitory activity was highest within the first 20 min of pepsin digestion and decreased upon subsequent digestion with pancreatin. An IC(50) value of 0.28 +/- 0.04 mg/mL was determined after 180 min of digestion, while no ACE inhibitory activity was measured for the undigested SPI at 0.73 mg/mL. Chromatographic fractionation of the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(93 citation statements)
references
References 28 publications
8
83
1
1
Order By: Relevance
“…The r 2 values determined between TEAC and IC 50 for antihypertensive activity (r 2 : À0.919), ORAC and IC 50 for antihypertensive activity (r 2 : À0.899) and IC 50 values for antihypertensive and antiproliferative activities (for 48 h) (r 2 : 0.827) also supported the relation among these bioactive properties. In the literature, inconsiderable ACE inhibitory activities were reported for commercial soybean protein isolate (Lo & Li-Chan, 2005), flaxseed meal protein isolate (Marambe, Shand, & Wanasundara, 2008) and pumpkin meal protein isolate (Vastag, Popovic, Popovic, Krimer, & Pericin, 2011) unless they were hydrolyzed by proteases. The ACE inhibitory potential of hazelnut protein extracts was also higher than that of protease digested pea protein isolate (1.36 mg/mL) and comparable with that of protease digested whey protein isolate (0.90 mg/mL) (Vermeirssen, Van Camp, & Verstraete, 2002).…”
Section: Antihypertensive Activity Of Isolated Proteinsmentioning
confidence: 99%
“…The r 2 values determined between TEAC and IC 50 for antihypertensive activity (r 2 : À0.919), ORAC and IC 50 for antihypertensive activity (r 2 : À0.899) and IC 50 values for antihypertensive and antiproliferative activities (for 48 h) (r 2 : 0.827) also supported the relation among these bioactive properties. In the literature, inconsiderable ACE inhibitory activities were reported for commercial soybean protein isolate (Lo & Li-Chan, 2005), flaxseed meal protein isolate (Marambe, Shand, & Wanasundara, 2008) and pumpkin meal protein isolate (Vastag, Popovic, Popovic, Krimer, & Pericin, 2011) unless they were hydrolyzed by proteases. The ACE inhibitory potential of hazelnut protein extracts was also higher than that of protease digested pea protein isolate (1.36 mg/mL) and comparable with that of protease digested whey protein isolate (0.90 mg/mL) (Vermeirssen, Van Camp, & Verstraete, 2002).…”
Section: Antihypertensive Activity Of Isolated Proteinsmentioning
confidence: 99%
“…In some studies, plant protein hydrolysates generated during pepsin digestion have potent ACE-inhibitory peptides. Lower ACE-inhibitory activity was found after subsequent digestion with pancreatin, suggesting that the active components were hydrolyzed [60,61]. For the pea proteins, high ACE-inhibitory activity is reached at the early stage of pepsin hydrolysis and the level is maintained during the small intestine phase using trypsin-chymotrypsin treatment [62].…”
Section: Production Of Peptidesmentioning
confidence: 99%
“…For instance, authors in references [155] and [47] utilized human digestive liquids to model digestion in vitro whereas several reports have concerned implementation of porcine enzyme mixtures [e.g. 60,127,132]. In addition to studying the resistance of antihypertensive peptide sequences against the digestive enzymes, the models have been utilized in order to produce bioactive peptides, plant derived ACE-inhibitory peptides among them.…”
Section: Bioavailabilitymentioning
confidence: 99%
“…In progressive chronic nephropathy, the ACEI enalapril exhibited beneficial effects on blood pressure control, renoprotection, and minimization of proteinuria ( 18 ). An in vitro study showed that many different peptides with ACE inhibitory activities were produced after pepsin-pancreatin digestion ( 19 ). Our previous studies also showed that SPH inhibited ACE activity in spontaneously hypertensive rats ( 9 ).…”
Section: Discussionmentioning
confidence: 98%